Frequency of Diabetic Acidosis Among Adult Patients Presenting at a Tertiary Care Hospital - Inam Ullah; Hanif, Shamimah; Fazal ur Rehman; Khan Panezai, Taimoor; Mansoor, Javeria; Mansoor, Nadia; Manzoor, Rida; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: DKA, a severe diabetes complication, is increasing, especially in low-income nations like Pakistan. Quetta lacks data on its local impact. Objective: To determine DKA prevalence in Quetta adults, analyze clinical signs, risk factors, and demographics, improving local understanding of the condition. Methods: 230 adult patients (≥18 years) with a diagnosis of diabetic ketoacidosis participated in a descriptive, cross-sectional study at a tertiary care hospital. Purposive sampling was used to choose patients based on predetermined inclusion criteria. Clinical assessments and patient interviews were used to gather data, with an emphasis on sociodemographic information, diabetes history, risk factors, and current symptoms. Results: Most patients (61.8%) were between the ages of 31 and 60, and most of them were male (55.7%). 43.9% had experienced diabetes for more than five years, and a sizable percentage (73%) had Type 2 diabetes. Infections (28.7%) and poor medication compliance (42.6%) were the main causes of DKA. Remarkably, newly diagnosed diabetics accounted for 14.8% of cases. Polyuria (63.9%), polydipsia (57.4%), vomiting (45.2%), and abdominal discomfort (38.3%) were the most common presenting symptoms. In 24.3% and 21.3% of patients, respectively, severe symptoms such altered awareness and Kussmaul breathing were noted. Conclusion: According to the results, poor compliance and infections are the main causes of the alarmingly high prevalence of diabetic ketoacidosis among Type 2 diabetic people in their prime. To lessen the burden and severity of diabetic acidosis, the study emphasizes the necessity of better diabetes education, early diagnosis, and standardized care regimens in areas like Quetta.